Surgical Approaches to Upper Limb Spasticity in Adult Patients: A Literature Review - Hashemi, Mahdis; Sturbois-Nachef, Nadine; Keenan, Marry Ann; Winston, Paul (Frontiers in Rehabilitation Sciences, 2021)
Introduction: Spasticity is the main complication of many upper motor neuron disorders. There are many studies describing neuro-orthopedic surgeries for correction of joint and limb deformities due to spasticity, though less in the upper extremity. The bulk of care provided to patients with spasticity is provided by rehabilitation clinicians however, few of the surgical outcomes have been summarized or appraised in the rehabilitation literature. Objective: To review the literature for neuro-orthopedic surgical techniques in the upper limb and evaluate the level of evidence for their efficacy in adult patients with spasticity. Method: Electronic databases of MEDLINE, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials and Cochrane Database of Systematic Reviews were searched for English, French as well as Farsi languages’ human studies from 1980 to July 2, 2020. After removing duplicated articles, 2855 studies were screened and 80 included based on the criteria. The studies were then divided into two groups, with 40 in each: trial and non-trial. The results of the 40 trial articles were summarized in 3 groups: shoulder, elbow & forearm and wrist & finger and each group subdivided based on types of intervention. Results: Level of evidence was evaluated by the Sackett approach. No Randomized Control Trial studies were found. Four studies for shoulder, 8 for elbow and forearm, 26 for wrist and finger (including 4 for thumb in palm deformity) and 2 systematic reviews were found. Two out of 40 trial articles were published in rehabilitation journals, one systematic review in Cochrane and the remaining 38 were published in surgical journals. Conclusion: Most surgical procedures are complex, consisting of several techniques based on patients’ problems and goals. This complexity interferes with the evaluation of every single procedure. Heterogenicity of participants and absence of clinical trial studies are other factors of not having a single conclusion. This review reveals that almost all the studies suggested good results after surgery in carefully selected cases with goals of reducing spasticity and improvement in function, pain, hygiene and appearance. A more unified approach and criteria is needed to facilitate a collaborative, evidence-based, patient referral and surgical selection pathway.